Qana – a Town of two Tragedies - Brylew, Marek (City and War, 2022)
Qana is a town located in the south of Lebanon, 14 km from Tyre, inhabited mostly by Shiʽite Muslims and a small number of Christians. According to the research of Lebanese historian Dr. Youssef El Hourany, Qana is known to have been the place where Jesus turned water into wine.However, for most Lebanese, Qana is associated with human suffering, martyrdom, and a symbol of resistance to Israel’s military aggression. In 1996, 106 people were killed in the town as a result of shelling by Israeli artillery. Ten years later, Israel attacked Qana again in an airstrike that resulted in the deaths of 27 more. Sixteen years after the tragedy, it is more and more difficult to find the causes, the course of events and generally – what exactly happened in Qana. As a participant and witness of those events, it is the author’s aim to revive the memory of the tragic fate of the inhabitants of that small town in southern Lebanon.